Boron-π-nitrogen-based conjugated porous polymers with multi-functions - Zhao, Wuxue; Zhuang, Xiaodong; Wu, Dongqing; Zhang, Fan; Gehrig, Dominik; Laquai, Frederic; Feng, Xinliang (Journal of Materials Chemistry A, 2013)
Two novel B-π-N based conjugated porous polymers have been successfully synthesized. The full characterization revealed their unique structures, both consisting of alternating π-bridged donor and acceptor subunits. They exhibited high chemical and thermal stabilities, with a weight loss of only 5% at 455°C and 362°C, respectively, on the basis of thermogravimetric analysis (TGA) (measured at a heating rate of 20°C min-1 under flowing N2). Their porous structures were confirmed by transmission electron microscopy (TEM) and nitrogen sorption analyses, revealing high surface areas of up to 1279 m2 g-1. The push-pull electronic structure of such a new type of porous polymer provided rich luminescent properties, solvatochromic emission and electrochemical activities. Furthermore, they showed multifunctions including effective H2 uptake capacities (at 1 bar and 77 K) of 143 cm3 g-1 (1.28 wt%) and 106 cm3 g-1 (0.95 wt%), respectively, fluorescence sensing and collection of fluoride anions. © The Royal Society of Chemistry.
CRIS-Team Scopus Importer:2023-03-20